2012
DOI: 10.1080/17470919.2011.596946
|View full text |Cite
|
Sign up to set email alerts
|

Through the eyes of the own-race bias: Eye-tracking and pupillometry during face recognition

Abstract: People are generally better at remembering faces of their own race than faces of a different race, and this effect is known as the own-race bias (ORB) effect. We used eye-tracking and pupillometry to investigate whether Caucasian and Asian face stimuli elicited different-looking patterns in Caucasian participants in a face-memory task. Consistent with the ORB effect, we found better recognition performance for own-race faces than other-race faces, and shorter response times. In addition, at encoding, eye movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
92
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 44 publications
8
92
7
Order By: Relevance
“…For example, an initial study by Blais, Jack, Scheepers, Fiset, and Caldara (2008) utilizing an eye tracker found that when presented with White and Asian faces, White participants fixated more on the eye region and Asian participants fixated more on the nose, regardless of the group membership of the target face (i.e., whether the face was an ingroup or outgroup member). In contrast, experiments by Goldinger, He, and Papesh (2009) and Wu, Laeng, and Magnussen (2012) demonstrated that White participants made more fixations and spent significantly more time attending to the eyes of White than Asian faces. In an additional study, Goldinger et al (2009) found comparable ingroup effects with Asian participants.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…For example, an initial study by Blais, Jack, Scheepers, Fiset, and Caldara (2008) utilizing an eye tracker found that when presented with White and Asian faces, White participants fixated more on the eye region and Asian participants fixated more on the nose, regardless of the group membership of the target face (i.e., whether the face was an ingroup or outgroup member). In contrast, experiments by Goldinger, He, and Papesh (2009) and Wu, Laeng, and Magnussen (2012) demonstrated that White participants made more fixations and spent significantly more time attending to the eyes of White than Asian faces. In an additional study, Goldinger et al (2009) found comparable ingroup effects with Asian participants.…”
mentioning
confidence: 77%
“…For example, whereas Goldinger et al (2009) found that the extent of overall eye movements and pupil dilation differed as a function of the Own Race Bias, they did not report similar analyses for attention to specific facial features such as the eyes. Furthermore, whereas Wu et al (2012) reported analyses on dwell times related to the eyes as a function of facial recognition, their results failed to demonstrate a significant relationship between target race (Asian vs. White), area of interest (including the eyes, nose, and mouth), and the Own Race Bias. Although the primary goal of the latter experiments was to better understand cognitive effort during encoding rather than attention to specific facial features, neither of these studies provide direct evidence related to the size or direction of a relationship between preferential attention to ingroup eyes and the Own Race Bias.…”
Section: Preferential Attention To the Eyes Of Ingroup Members 27mentioning
confidence: 88%
See 3 more Smart Citations